الازعاج في القانون الانكليزي: دراسة تحليلية مقارنة مع القانون المدنى العراقي - علي، يونس صلاح الدين (جامعة الموصل - كلية الحقوق, 2014)
Nuisance is considered as one of the civil torts in the English law as well as such other torts as negligence, trespass to land, trespass to persons and defamation. It is worth bearing in mind that all of the torts are included in the English law of torts, which is an unwritten law based upon judicial precedents of the English courts. The study aims at explaining the nuisance elucidating its legal base upon which the legal liability of civil tort is based as well as clarifying its various aspects, such as noise, malodor, vapour, smoke environmental pollutants and comparing this base with that upon which the legal responsibility arising from harassment and nuisance in Iraqi civil law is based.
يعد الإزعاج أحد أنواع الأخطاء المدنية في القانون الإنكليزي فضلا عن أخطاء مدنية أخرى وردت في هذا القانون على سبيل الحصر كالإهمال والتعدي على العقار والتعدي على الأشخاص والقذف أو التشهير. وقد وردت هذه الأخطاء فيما يعرف بقانون الأخطاء المدنية الإنكليزي (law of torts) وهو قانون غير مكتوب مبني على السوابق القضائية للمحاكم الإنكليزية. وتهدف هذه الدراسة إلى التعرف على الإزعاج بوصفه خطأ مدنيا وبيان أنواعه والأساس القانوني الذي تستند عليه المسؤولية المدنية الناجمة عنه وعن صوره المختلفة كالضوضاء والروائح الكريهة والدخان وملوثات البيئة ومقارنة هذا الأساس بالأساس القانونية للمسؤولية المدنية التي تنجم عن الإزعاج والمضايقات الأخرى في القانون المدني العراقي.
Keywords: القانون المدني -- القانون الانجليزي -- العراق -- المحاكم